Kebijakan Promosi Selama Pembatasan Sosial Berskala Besar di The Sultan Hotel & Residence, Aryaduta Suites Semanggi dan Grandhika Iskandarsyah - Asep Parantika; Sheyla Juliandra (STIEPAR YAPARI Bandung, 2021)
In early 2020, the entire world suffered the Covid-19 Pandemic which impacted the hotel industry enormously. One of the impacts felt by several hotels was a decline in hotel occupancy, resulting in a quite shortfalls. To suppress the increasing number of Covid-19 virus cases, the regional government of DKI Jakarta Province has implemented a Large-Scale Social Ristictions Policy (PSBB). Hence, the objectives of this study are (1) to find out the impacts on hotels’ during the PSBB period, (2) to find out hotel’s promotion policy during the Covid-19 pandemic (3) to find out the outcomes of hotels’ promotion policy implementation during the Covid-19 pandemic. This study uses qualitative research with a descriptive approach. Data collection techniques are used by conducting interviews and documentation studies. The results showed that hotel industry undergone a tremendous impact, one of which was the decrease in hotel occupancy. Some hotels have developed some promotion policy to keep their operation wheels moving. The following is the hotel promotion policy, including creating a “Work From Hotel” package or working in a hotel, namely by designing hotel rooms as personal offices equipped with fast Wi-Fi, selling 3 night packages for 2 nights including 2 breakfast, selling complete sanitation packages for living quarters, offices, houses of worship, schools or other areas, selling food in boxes that can be delivered to the destination and selling the